2001
DOI: 10.1103/physrevb.64.134208
|View full text |Cite
|
Sign up to set email alerts
|

Metastable transformation states of decagonal Al-Co-Ni due to inhibited decomposition

Abstract: The transformation behavior of high-Co decagonal Al-Co-Ni is studied. Starting from stability considerations based on a number of annealing treatments we check theoretical predictions of the stabilization mechanism and transformation mechanism by phason strain analysis and tiling analysis. The quasicrystal transforms in the first stages into nanodomain structures and finally decomposes into a quasicrystal and a normal crystalline phase. Before decomposition, the material is locked in a disordered state exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…5D structure model based on the atomic surfaces modelling method; P10, wR ¼ 0.060 for 2767 reflections (Cervellino, Haibach, Steurer, 2002). According to Döblinger, Wittmann, Grushko (2001) the superstructure type II is not a d-phase but corresponds to an orientationally fivefold twinned nanodomain structure. According to several in situ HT X-ray diffraction studies (Baumgarte, Schreuer, Estermann, Steurer, 1997;Steurer, Cervellino, Lemster, Ortelli, Estermann, 2001), the HT-phase is a quasiperiodic phase without superstructure reflections.…”
Section: Alconi-chs-02mentioning
confidence: 99%
See 1 more Smart Citation
“…5D structure model based on the atomic surfaces modelling method; P10, wR ¼ 0.060 for 2767 reflections (Cervellino, Haibach, Steurer, 2002). According to Döblinger, Wittmann, Grushko (2001) the superstructure type II is not a d-phase but corresponds to an orientationally fivefold twinned nanodomain structure. According to several in situ HT X-ray diffraction studies (Baumgarte, Schreuer, Estermann, Steurer, 1997;Steurer, Cervellino, Lemster, Ortelli, Estermann, 2001), the HT-phase is a quasiperiodic phase without superstructure reflections.…”
Section: Alconi-chs-02mentioning
confidence: 99%
“…The transformation behavior of a homogenized (1290 K, 43 h) and annealed (1140 K, 384 h, 1125 h, 2718 h) sample with composition Al 72.5 Co 15.5 Ni 12 was studied by SAED and HRTEM (200 kV) (Döblinger, Wittmann, Grushko, 2001). It was found that a homogenous d-phase (superstructure type S1) of this composition transforms via intermediate states (such as 'superstructure type II', which resulted to show first a fivefold twinned 1D QC and then a twinned h4,6i-approximant) to a mixture of the monoclinic X-phase and a d-phase (superstructure type I, unfinished transition probably due to not equilibrated chemical order) after 2718 h at 1140 K. This kind of transformation has been predicted by Steurer (1999Steurer ( , 2000 and Honal, Haibach, Steurer (1998).…”
Section: Electron Microscopy -Co Rich D-phasesmentioning
confidence: 99%
“…These NDS's are not necessarily periodic in three dimensions, multiply twinned 1D QC's 8 or states whose order according to a 1D QC is only partially developed were also observed. 9 There is still a lack of experimental data about the transition of NDS's to larger domains of periodic approximants.…”
Section: Introductionmentioning
confidence: 99%
“…10,22,23 NDS's were observed in the system AlNi-Co by high-resolution x-ray diffraction 8,24,25 and highresolution transmission electron microscopy ͑HRTEM͒. 9 At compositions close to the binary Al-Co line the phase diagram seems to be very complicated. 26 Pentagonal quasicrystals are reported 27,28 to exist between Al 73 Ni 7 Co 20 and Al 72.5 Ni 10 Co 17.5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation